(untitled) (Research, Society and Development, 2022)
Introduction: Diabetes mellitus is a disease characterized by increased blood glucose levels. Due to its high prevalence, it is considered a public health problem. Objective: To present information, clinical findings and control over Diabetes Mellitus, clarify conducts to be applied during dental care to diabetic patients. In addition to exposing acute and chronic complications and their respective dental interventions that can be done in the face of a complication during the care of diabetic patients. Method: To carry out this literature review, searches were carried out on the PubMed, SciELO, Google Scholar, electronic library of the Ministry of Health, to choose articles published between the years 2000 to 2022. Conclusion: During dental care for diabetic patients type I and type II, the main approach should always be to analyze whether the patient has the disease under control, so that care can be provided. The dentist should be able to assess the risks that may occur during care for this patient, know how to reverse complications related to diabetes mellitus, and identify whether there is a health risk.